Site fidelity and migration patterns of the Southern Streaked Flycatcher breeding in urban and rural areas of Brazil - Barbosa, Karlla Vanessa Camargo; Costa, Thiago Vernaschi Vieira; Ribeiro, Milton Cezar; Jahn, Alex Edward (Frontiers in Bird Science, 2023)
The Southern Streaked Flycatcher (Myiodynastes maculatus solitarius) is a common Neotropical austral migrant that breeds in both rural and urban environments of southeastern Brazil, providing a model to understand how songbirds are responding to an increasingly urban landscape in this region of the continent. We evaluated whether breeding site fidelity is related to sex and habitat type (urban versus rural). Because the annual cycle of migratory birds provides context to breeding season processes, we also described their migration timing and routes, and location of the non-breeding sites.Between 2016 and 2021, we captured, banded, and deployed GPS archival tags on Southern Streaked Flycatchers, and conducted systematic monitoring of 61 individuals in rural and urban areas in southeastern Brazil. Our results revealed that this population migrates from the Atlantic Forest to Amazonia, spending 15-40 days on fall migration. Moreover, we found i) that overall return rates to breeding sites are high (>52%), ii) that return rates did not vary with sex, and iii) that return rates varied with body condition and habitat, with birds in better condition having higher return rate in rural but not urban areas. More individual-level research on migratory birds in South American urban areas promises a novel perspective on how Neotropical austral migrants are responding to a rapidly changing landscape, and to inform future conservation initiatives in the increasingly expanding urban areas of southern Brazil.